Threshold concepts in women's and gender studies ways of seeing, thinking, and knowing - Launius, Christie; Hassel, Holly (Routledge Books, 2022)
Threshold Concepts in Women's and Gender Studies: Ways of Seeing, Thinking, and Knowing is a textbook designed primarily for introduction to Women's and Gender Studies courses with the intent of providing both a skill- and concept-based foundation in the field. The third edition includes fully revised and expanded case studies and updated statistics; in addition, the content has been updated throughout to reflect significant news stories and cultural developments. The text is driven by a single key question: "What are the ways of thinking, seeing, and knowing that characterize Women's and Gender Studies and are valued by its practitioners?". This book illustrates four of the most critical concepts in Women's and Gender Studies-the social construction of gender, privilege and oppression, intersectionality, and feminist praxis-and grounds these concepts in multiple illustrations. Threshold Concepts develops the key concepts and ways of thinking that students need to develop a deep understanding and to approach material like feminist scholars do, across disciplines"--